2020
DOI: 10.1371/journal.pone.0238723
|View full text |Cite|
|
Sign up to set email alerts
|

Non-GABA sleep medications, suvorexant as risk factors for falls: Case-control and case-crossover study

Abstract: The aim of this study was to examine the risk of falls associated with the use of non-gamma amino butyric acid (GABA) sleep medications, suvorexant and ramelteon. This case-control and case-crossover study was performed at the Kudanzaka Hospital, Chiyoda Ward, Tokyo. A total of 325 patients who had falls and 1295 controls matched by sex and age were included. The inclusion criteria for the case group were hospitalized patients who had their first fall and that for the control were patients who were hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
0
28
1
Order By: Relevance
“…Retrospective case–control and case–crossover studies were carried out at Kudanzaka Hospital (231 beds) in Chiyoda‐ward, Tokyo, Japan. We collected data of hospitalized patients (case group) who experienced their first falls when hospitalized between January 2016 and November 2018 18 . No exclusion criteria, such as age, departments and falls before hospitalization, were applied to the case group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective case–control and case–crossover studies were carried out at Kudanzaka Hospital (231 beds) in Chiyoda‐ward, Tokyo, Japan. We collected data of hospitalized patients (case group) who experienced their first falls when hospitalized between January 2016 and November 2018 18 . No exclusion criteria, such as age, departments and falls before hospitalization, were applied to the case group.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was determined based on the number of falls collected during the recruitment period. In determining the sample size to be used in this study, we used the size of the fall group determined by a previous study that examined the risk of falls due to sleep medications 18 . The association between medications use and falls was assessed by conditional logistic regression analysis using odds ratio (OR) and a 95% confidence interval (CI).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding suvorexant, Torii et al reported that suvorexant was not significantly associated with falls (odds ratio [OR] = 0.25, 95% confidence interval [CI] = 0.06–1.06) 10 . However, Ishibashi et al found that the drug significantly increased the fall risk (OR = 2.61, 95% CI = 1.29–5.28) 11 . Similarly, the effects of suvorexant on fall risk have also been inconsistent in prior research.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…For this reason, ramelteon is mostly used clinically in the treatment of chronic insomnia [ 10 ]. In addition, as ramelteon does not bind to neurotransmitter receptors, it has been revealed to avoid the distraction associated with neurotransmitter receptor drugs and thus has no potential for drug addiction or dependence [ 11 ]. However, ramelteon has anti-inflammatory and antioxidant properties, and ameliorates cellular damage [ 12 ].…”
Section: Introductionmentioning
confidence: 99%